POSITIVE AND NEGATIVE SUPERHUMPS OF THE DWARF NOVA MN DRA - Samsonov, D. A.; Pavlenko, E. P.; Andreev, M. V.; Sklyanov, A.; Zubareva, A. M.; Voloshina, I. B.; Metlov, V. G.; Shugarov, S. Yu.; Golovin, A. V.; Antoniuk, O. I. (Одеські астрономічні публікації, 2010)
We present the result of O–C analysis of the dwarf nova MN Dra. It is based on the multi-site photometric observations that were made over 77 nights in August – November, 2009. The total exposure was 433 hours. During this time binary underwent two superoutbursts and five normal outbursts. In superoutbursts the positive superhumps decreased with extremely large P = -(3 - 8) x 10-4 for SU UMa-like dwarf novae, confirming the known behavior of MN Dra in 2003. MN Dra displayed large-amplitude (up to 1.4m in quiescence and 0.1m–0.2m in normal outbursts) negative superhumps. The improved value of negative superhump period is 0.095952(4) d.